Capacity building in livestock breeding and genetic improvement in achieving UN Sustainable Development Goals for Africa - Tiambo, Christian K.; Opoola, O.; Okpeku, M.; Houaga, I.; Touko, B.A.H.; Dessie, Tadelle (Springer, 2025)
To achieve the Sustainable Development Goals of the United Nations (UN-SDGs) in Africa, livestock breeding efficiency is a prerequisite. Human capital in the form of professional, managerial, and technical skills, improved policies and institutional operation are the key enablers of performance for the smallholder livestock sector. Capacity building is central to guarantee African livestock efficiency along the value chains and ultimately transformed livelihoods. Currently, animal breeding and genetic improvement in Africa are constrained by a serious human and institutional capacity gap. The Livestock Development Strategy for Africa (LiDESA) seeks to transform the livestock sector for accelerated and equitable growth and for enhanced contribution to socio-economic development. Sustainable livestock development in Africa could be better realized through the development of customized capacity building strategies targeting (1) relevant participatory breeding education, hands-on training, efficient technical assistance, and collaborations / partnerships aiming to address farmers’ present and future challenges, (2) enabling breeding systems for sustainable productivity, resilience of breeds, and animal seed stock management, and (3) market-led breeding solutions that are attractive for the younger and future generations.